Bond Restructuring and Moral Hazard : Are Collective Action Clauses Costly? - Becker, Torbjorn (IMF Working Papers; Working Paper ;, 2001)
Many official groups have endorsed the wider use by emerging market borrowers of contract clauses which allow for a qualified majority of bondholders to restructure repayment terms in the event of financial distress. Some have argued that such clauses will be associated with moral hazard and increased borrowing costs. This paper addresses this question empirically using primary and secondary market yields and finds no evidence that the presence of collective action clauses increases yields for either higher- or lower-rated issuers. By implication, the perceived benefits from easier restructuring are at least as large as any costs from increased moral hazard.